Compound of the Harsha Bhairon shrine - Temples of India Project Team (Jio Institute, 2024)
Several pillars dating back to the 10th century CE were reused in various late medieval and modern structures within the compound of the Harsha Bhairon shrine. Additionally, several sculptures were affixed on the walls of the compound.